The Effect of Short-Term Sport-Specific Strength and Conditioning Training on Physical Fitness of Well-Trained Mixed Martial Arts Athletes. - Kostikiadis, Ioannis N; Methenitis, Spyridon; Tsoukos, Athanasios; Veligekas, Panagiotis; Terzis, Gerasimos; Bogdanis, Gregory C (J Sports Sci Med, 2018)
The purpose of the present study was to investigate the effect of a short-term, high-intensity, low-volume Mixed Martial Arts (MMA) specific strength and conditioning training program on performance in national level MMA athletes. Seventeen experienced fighters were divided into two groups: (A) Specific Training Group (STG; n = 10), which followed a specific strength and conditioning program designed according to the demands of MMA competition and (B) Regular Training Group (RTG; n = 7), in which participants followed a regular strength and conditioning program commonly used by MMA athletes. Before and after the four-week training period (3 days per week), body composition, aerobic fitness, strength, power and speed were evaluated. Significant improvements in estimated VO, average power during the 2000 m rowing, bench press, back squat and deadlift 1RM, SJ power, CMJ height power, medicine ball throw velocity, 10 m sprint and 2 m take down speed and fat-free mass were found only in the STG (3.7 to 22.2%; p < 0.05; Hedge's g = -0.42 - 4.1). No significant changes were found for the RTG (p = 0.225 to 0.811). Significant differences between the groups were found for almost all post-training assessments (p < 0.05; Hedge's g = 0.25 - 1.45) as well as for the percentage changes from pre to post training (p < 0.05; Hedge's g: 0.25 - 1.45). Significant relationships were found between percentage changes in fat-free mass, endurance capacity, muscle strength/power and speed (r: -0.475 to 0.758; p < 0.05). These results suggest that a high-intensity low-volume strength and conditioning training intervention designed according to the demands of MMA competition may result in significant performance improvements for well-trained fighters.